MiR-29b-3p Inhibits Migration and Invasion of Papillary Thyroid Carcinoma by Downregulating COL1A1 and COL5A1 - Wang, Congjun; Wang, Ye; Fu, Zhao; Huang, Weijia; Yu, Zhu; Wang, Jiancheng; Zheng, Kaitian; Zhang, Siwen; Li, Shen; Chen, Junqiang (Frontiers in Oncology, 2022)
Introduction MicroRNAs (miRNAs) are small noncoding RNA molecules that regulate genetic expression and are also vital for tumor initiation and development. MiR-29b-3p was found to be involved in regulating various biological processes of tumors, including tumor cell proliferation, metastasis, and apoptosis inhibition; however, the biofunction and molecule-level mechanisms of miR-29b-3p inpapillary thyroid carcinoma (PTC) remain unclear. Methods The expression of miR-29b-3p in PTC samples was tested via qRT-PCR. Cellular proliferation was analyzed by CCK-8 and EdU assays, and cellular migratory and invasive abilities were assessed utilizing wound-healing and Transwell assays. In addition, protein expressions of COL1A1, COL5A1, E-cadherin, N-cadherin, Snail, and Vimentin were identified via Western blot (WB) assay. Bioinformatics, qRT-PCR, WB, and dual luciferase reporter assays were completed to identify whether miR-29b-3p targeted COL1A1 and COL5A1. In addition, our team explored the treatment effects of miR-29b-3p on a murine heterograft model. Results Our findings revealed that miR-29b-3p proved much more regulated downward in PTC tissue specimens than in adjacent non-cancerous tissues. Meanwhile, decreased expression of miR-29b-3p was strongly related to the TNM stage of PTC patients (p<0.001), while overexpression of miR-29b-3p in PTC cells suppressed cellular migration, invasion, proliferation, and EMT. Conversely, silencing miR-29b-3p yielded the opposite effect. COL1A1 and COL5A1 were affirmed as the target of miR-29b-3p. Additionally, the COL1A1 and COL5A1 were highly expressed in PTC tumor samples than in contrast to neighboring healthy samples. Functional assays revealed that overexpression of COL1A1 or COL5A1 reversed the suppressive role of miR-29b-3p in migration, invasion, and EMT of PTC cells. Finally, miR-29b-3p agomir treatment dramatically inhibited Xenograft tumor growth in the animal model. Conclusions These findings document that miR-29b-3p inhibited PTC cells invasion and metastasis by targeting COL1A1 and COL5A1; this study also sparks new ideas for risk assessment and miRNA replacement therapy in PTC.